Rapid and Robust Continuous Purification of High-Titer Hepatitis B Virus for In Vitro and In Vivo Applications - Jochen M. Wettengel; Bianca Linden; Knud Esser; Michael Laue; Benjamin J. Burwitz; Ulrike Protzer (Viruses, 2021)
Available treatments for hepatitis B can control the virus but are rarely curative. This led to a global initiative to design new curative therapies for the 257 million patients affected. Discovery and development of these new therapies is contingent upon functional in vitro and in vivo hepatitis B virus (HBV) infection models. However, low titer and impurity of conventional HBV stocks reduce significance of in vitro infections and moreover limit challenge doses in current in vivo models. Therefore, there is a critical need for a robust, simple and reproducible protocol to generate high-purity and high-titer infectious HBV stocks. Here, we outline a three-step protocol for continuous production of high-quality HBV stocks from supernatants of HBV-replicating cell lines. This purification process takes less than 6 h, yields to high-titer stocks (up to 1 × 1011 enveloped, DNA-containing HBV particles/mL each week), and is with minimal equipment easily adaptable to most laboratory settings.